Zróżnicowanie bieżącego przyrostu sosen w trzech klasach wieku - Kaźmierczak, Katarzyna (Leśne Prace Badawcze, 2013)
The study presents the results of an analysis of the pine tree growth increments (height increment, dbh increment, basal area increment and volume increment) for a 5-year period. The study involved Scots pine trees of Kraft’s class 1, 2 and 3 (dominant stand) in stands of different age classes (II, III, V) growing in fresh mixed coniferous (BMśw) and fresh coniferous (Bśw) forest habitats. The multivariate analysis of variance was performed to assess the statistical significance of age and dominance of trees within a stand on their increment. The dominance position was classified for each tree using Kraft’s criteria. The following characteristics were also measured: dbh of the trunk in two directions (N-S and W-E), and crown projection area on the basis of the characteristic tree crown points, projected using of a crown projector, characteristic points in tree crowns (7 to 14 on average). The actual height was determined after trees were felled. The following measurements of the single tree growing space were selected and determined: crown projection area – p k (m 2 ), crown diameter – d k (m), Seebach’s growth space number – d k / d 1.3 , crown projection area to basal area ratio – d 2 k / d 2 1.3 , crown deflection coefficient – d k / h , single tree space – ppd = pkh (m 3 ). We assessed the strength of the relationships between tree growth parameters and tree growth space, crown length, relative crown length and slenderness. Both the age and dominance position of trees within the stand affected the growth increments. The strongest correlation among measured traits was between the 5-year volume increment and decreasing slenderness.